(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to prepare special planning exercises for playing situations in raising the cognitive efficiency index for some technical skills of volleyball players aged (16-18 years). The researchers used the experimental method for the two equal groups (hermetic control) with a pre and posttest for its relevance to the nature of the research. The research community represents a group of (12) players affiliated with the Al-Daghara Sports Club. As for the control group, it was the group of Al-Rumaitha club players, which numbered (12) players and were of the same age as the experimental group. The researchers prepared planning exercises for playing situations according to a program that was applied for a period of (10) weeks And by three training units per week, after implementing the training program and conducting the pre and posttests that were used for the first time at the country level. The researchers reached several conclusions, the most important of which is that the tactical exercises similar to the playing positions had an effect in raising the cognitive efficiency index for some technical skills. It is clear in these two skills, and the experimental group was distinguished in the post-tests, which are among the most important tests that work with nanotechnology and artificial intelligence. Using the (mindwave nerusky) device in the analysis of peripheral cognitive efficiency, which works within the levels set by the International Volleyball Federation.